2023
DOI: 10.1002/adfm.202300184
|View full text |Cite
|
Sign up to set email alerts
|

Biomorphic Actuation Driven Via On‐Chip Buckling of Photoresponsive Hydrogel Films

Abstract: Remotely controllable photoresponsive hydrogel actuators are promising for applications in multiple fields. However, simple deformation mechanisms, which rely on the general swelling/deswelling, limit their performance and application. Herein, we report a displacement amplification mechanism based on the buckling deformation of photoresponsive hydrogel film. The on‐chip buckled architecture of the hydrogel enables actuation between a flat 2D shape and tubular 3D buckled shape with remarkable performances, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…It has been reported that the inclusion of light absorbers in the thermoresponsive hydrogel can change the wavelength where the hydrogel shows a light response. , As an example of imparting visible or near-infrared light responsiveness to poly­( N -isopropylacrylamide) (PNIPAM) hydrogels, previous studies have reported the method of including metal nanoparticles to a thermoresponsive hydrogel. Notably, the multiphoton photoreduction allows for the patterning of microstructures composed of metal nanoparticles within a thermoresponsive hydrogel, enabling spatially selective and high-resolution responsiveness to light stimuli in the visible and near-infrared wavelengths. The light responsiveness of hydrogels is determined by the density of metal nanoparticles generated within the hydrogel, which serves as a light absorber.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the inclusion of light absorbers in the thermoresponsive hydrogel can change the wavelength where the hydrogel shows a light response. , As an example of imparting visible or near-infrared light responsiveness to poly­( N -isopropylacrylamide) (PNIPAM) hydrogels, previous studies have reported the method of including metal nanoparticles to a thermoresponsive hydrogel. Notably, the multiphoton photoreduction allows for the patterning of microstructures composed of metal nanoparticles within a thermoresponsive hydrogel, enabling spatially selective and high-resolution responsiveness to light stimuli in the visible and near-infrared wavelengths. The light responsiveness of hydrogels is determined by the density of metal nanoparticles generated within the hydrogel, which serves as a light absorber.…”
Section: Introductionmentioning
confidence: 99%